Buchnera breaks the specialization of the cotton-specialized aphid (Aphis gossypii) by providing nutrition through zucchini - Xu, Weili; Liu, Weijiao; Li, Jinming; Zhu, Xiangzhen; Wang, Li; Li, Dongyang; Zhang, Kaixin; Ji, Jichao; Gao, Xueke; Luo, Junyu; Cui, Jinjie (Frontiers in Nutrition, 2023)
The cotton aphid, Aphis gossypii Glover, is a species of polyphagous aphid with many biotypes, and its host transfer has always been the focus of research on the control of cotton aphid. An important factor affecting aphid specialization is the nutritional association with microbial symbionts that provide the host with nutrients lacking in the discomfort diet. We analyzed the microbial composition and biodiversity of reared on zucchini for 10 generations (T1–T10) and cotton as a control (CK), by high-throughput Illumina sequencing of 16S ribosomal RNA genes. The findings showed that the change in plant hosts decreased the richness and variety of microbial species. Regardless of whether the plant host is altered or not, Proteobacteria and Firmicutes are the predominate phyla in cotton-specialized aphid. Additionally, cotton-specialized aphids that live in zucchini had considerably lower relative abundances of non-dominant phyla (Bacteroidetes) than cotton hosts. At the genus level the dominant communities were Buchnera, Acinetobacter, and Arsenophonus. The relative abundance of Buchnera was significantly higher in aphids reared on zucchini than those on cotton, whereas the opposite was observed for Acinetobacter, as well as for some non-dominant communities (Stenotrophomonas, Pseudomons, Flavobacterium, Novosphingobium). Collectively, this study clarifies the dynamic changes of symbiotic bacteria in cotton-specialized aphi reared on zucchini for multiple generations. Among them, Buchnera is crucial for the cotton-specialized aphid to get nutrients during the transfer of the host and has a favorable impact on the colonization of cotton-specialized aphid populations on zucchini hosts. It not only enriches our understanding of the relationship between the bacterial microbiota of aphids and their adaptability to new hosts, zucchini, but also expands the current body of research on the mechanisms underlying the host shifting ability of cotton-specialized aphids.